Evaluation of Outcome of ORIF by DCP Vs LCP in Mid-Shaft Fractures of Radius – Ulna in A Secondary Level Hospital of Bangladesh (Journal of Shaheed Suhrawardy Medical College, 2020)
Purpose: To compare the result of mid-shaft fracture radius and ulna treated by small DCP and LCP.Methods: Prospective interventional study, done in the Department of Orthopaedic Surgery, 250 Bedded General Hospital, Tangail from January, 2017 to December, 2018. The study was carried out with sample size 30 patients of mid-shaft fracture of radius and ulna. Out of them 15 were treated by DCP and screws and 15 patients were treated by LCP and screws.Results: In this study mean age in group I was 32.63±9.42 and in group II was 37.54+7.12. Male patients were 17 and female were 13 in number. Motor vehicle accident was the commonest cause of fracture found in 60% in group-I and 73.33% in group-II. In group-I, out of 15 cases all cases (100%) united with mean time of 15.87 ± 3.89 weeks. In group-II, out of 15 cases all (100%) cases united with the mean time of 14.0 ± 2.27 weeks. There was no major complication in both groups. Regarding the final outcome, excellent results in group-I were achieved with 11 (73.33%) cases while in group-II with 12 (80.00%) cases. Satisfactory results were seen in 04 (26.67%) cases in group-I and 03 (20.00%) cases in group-II.Conclusion: On the statistical point of view there was no significant difference between dynamic compression plate group and locking compression plate group for the treatment of mid-shaft fracture radius and ulna.J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 106-109